Exploring childrens’ understanding of overweight and obesity: a qualitative study in Santiago, Chile - Prieto Bravo, Cecilia Luisa (The University of Edinburgh, 2025)
This thesis explores the understanding and experiences of overweight and obesity in children aged 10-12 from 3 clinics located in a deprived area in Santiago, Chile. Overweight and obesity are considered to be a risk to the health of both individuals and the population as a whole. Indeed, in the last three decades, overweight and obesity have been framed as an ‘epidemic’ and linked to severe risks and comorbidities such as diabetes, cardiovascular disease and cancer. There is a high prevalence of overweight and obesity in Chile, and public health strategies have been developed to address this. Particular concerns have been raised about children. According to the last report from the Subsecretaria de Salud Publica (2023), 58.3% of Chilean children are categorised as ‘overweight’ or ‘obese’. Despite the country’s economic growth, social and health inequalities remain among the child population in terms of the distribution of overweight. Most studies on childhood obesity are epidemiological, quantitative studies that provide information on biomarkers, trends in Body Mass Index, and health risks. However, there are gaps in the existing research that this thesis sought to address. This research is need it for several reasons: first, there is limited insight into the perceptions and experiences of children who have been clinically labelled as obese. Second, while some research has addressed the views of parents in relation to children’s overweight, it is less common for these views to be sought alongside the views of their child. Third, much research on childhood obesity comes from the Global North. Considering these gaps, this research explores overweight and obese children’s and mothers’ meanings of health, and weight, and their everyday Health-Related Practices (HRPs) related to weight to make potential contributions to public health strategies regarding overweight and obesity in children. This qualitative study, conducted in Santiago between March and September 2021, involved 34 semi-structured online separate interviews with children aged 10-12 who were classified as ‘overweight’ or ‘obese’ (N=18) and their mothers (N=16). Participants were recruited from 3 clinics (ANCORA). Children and mothers were each interviewed once. Due to the COVID-19 lockdowns, interviews were conducted online, and different participatory methods and prompts were used to encourage participants’ engagement. The methods used to explore meanings of bodies, weight and HRPs with dyads provided insights into complex perspectives of child-mother dyads and family dynamics, shedding light on relational aspects and differing levels of children’s agency. The use of participatory methods in interview design and the approach to online data collection facilitated the exploration of sensitive topics with children and caregivers. Employing Reflexive Thematic Analysis, the researcher analysed the interview data, drawing on relevant concepts from the sociology of health and illness, and the sociology of childhood, to interpret the accounts of children and mothers. The analysis explored the children’s accounts collectively, but also looked at the child/mother dyads to uncover any shared accounts, gaps or silences. The thesis presents five key findings. First, children’s descriptions of their bodies differed from the medical terms ‘overweight’ and ‘obese’. None of the children and only one mother used the term ‘obese’. For most children and mothers, ‘overweight’ labels were not significant in terms of having a ‘disease’ or an ‘ill health’ condition that may be ‘treated’. Children’s meanings of growth and weight were shaped by social interactions that contextually shaped their perspectives of their own weight and body, focusing on appearance rather than health. Second, children faced weight stigma and experienced negative emotions associated with weight-shaming from clinicians, peers and relatives. In clinical settings, children reported becoming more aware of their body size, and most began to perceive their bodies as ‘different’. How others evaluated weight was relevant to the children, particularly when someone else noticed that being ‘overweight’ was a ‘problem’. Third, children’s HRPs related to food and physical activity (PA) were understood as individual responsibilities and medicalised practices to lose weight. Children and mothers engaged in weight monitoring and surveillance practices, often with perceived emotional impacts. Strategies such as food type and quantity restriction were commonly used to achieve or maintain a ‘healthy’ weight. PA was predominantly described as an activity to burn calories and lose weight, rather than for general health or well-being. Fourth, findings demonstrate that social determinants of health (SDoH), such as socioeconomic circumstances, gender, and living and working conditions, influenced food choices and PA opportunities. For instance, lack of income or unemployment constituted critical barriers to achieving the required ‘healthy diet’, while material circumstances, such as housing and home environments, also determined PA opportunities. Fifth, children and mothers understood public health messages from interventions such as front-of-pack labelling (FOP) and the ‘Choose to live healthy’ strategy. However, they experienced barriers to adopting these interventions due to socioeconomic factors and family dynamics. This thesis provides insight into children’s views on overweight and obesity, and the HRPs adopted to address their weight. It emphasises the importance of understanding children’s meanings and experiences, and their implications for public health and practice: first, clinics should move towards a health approach that is not focused exclusively on weight and aims to reduce weight stigma; second, clinicians should consider how best to engage with children as individuals, encouraging them to be more involved in decision-making about their own health; third, clinicians should consider children’s everyday routines, and not assume families are all the same; fourth, clinicians should seek to be aware of families’ social and economic contexts when recommending changes to diet and PA. By considering children’s and mother’s experiences and meanings of health, growth, weight, and everyday family HRPs, it is possible to present a more complex picture of, and challenge the assumptions around, health, growth, weight, and HRPs in the context of overweight and obesity.
Keywords: Children; Overweight; Obesity; Stigma; Health-Related Practices; Qualitative Research